2008
DOI: 10.1086/521973
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Generations of Refractory Inclusions in the Metal‐Rich Carbonaceous Chondrites Acfer 182/214 and Isheyevo

Abstract: Ca,Al-rich inclusions (CAIs) are believed to have formed by evaporation, condensation, and melting of the pre-existing solids during the earliest stages of the solar system evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(119 citation statements)
references
References 41 publications
4
115
0
Order By: Relevance
“…Several observations suggest that these meteorites may have accreted a significant fraction of pristine material of possible outer Solar System origin. CH chondrites contain the highest abundance of early-formed 26 Al-poor CAIs (17); these solids are inferred to have been transported to larger radial distances from the Sun compared with the later-formed 26 Al-rich CAIs. In addition, CH chondrites have incorporated chondrite lithic clasts characterized by 15 N-rich (up to 1,000‰) compositions (18,19), which are thought to be indicative of lowtemperature environments that existed in the outer Solar System (20)(21)(22).…”
Section: Isotopic Evidence For Primordial Molecular Cloud Mattermentioning
confidence: 98%
“…Several observations suggest that these meteorites may have accreted a significant fraction of pristine material of possible outer Solar System origin. CH chondrites contain the highest abundance of early-formed 26 Al-poor CAIs (17); these solids are inferred to have been transported to larger radial distances from the Sun compared with the later-formed 26 Al-rich CAIs. In addition, CH chondrites have incorporated chondrite lithic clasts characterized by 15 N-rich (up to 1,000‰) compositions (18,19), which are thought to be indicative of lowtemperature environments that existed in the outer Solar System (20)(21)(22).…”
Section: Isotopic Evidence For Primordial Molecular Cloud Mattermentioning
confidence: 98%
“…Injection during the solar nebula stage (i.e., protostar Class II, equivalently, a classical T Tauri star) may not be optimal because the small radius of the disk (∼30-45 AU) requires a nearby (∼0.3 pc) SNII to provide sufficient 26 Al, that potentially would disintegrate the solar nebula (Gounelle & Meibom 2008). Furthermore, the CAI-forming epoch could have been as short as 2 × 10 4 -10 5 yr according to radiometric dating (Bizzarro et al 2004;Thrane et al 2006;Krot et al 2008), presumably because sufficiently high temperatures for CAI formation only were met during the Class 0 and early Class I stages. These stages only last for ∼10 4 yr and ∼10 5 yr (André & Montmerle 1994).…”
Section: Radioactive Aluminum-26 In the Outer Solar Systemmentioning
confidence: 99%
“…Isotopic analyses are much needed to gain additional constrains on the formation of CAIs in SaU 290. Krot et al (2008) inferred that some more refractory inclusions (composed mainly of hibonite, grossite, Al-rich pyroxene, perovskite, and gehlenitic melilite) in one CH chondrite and a CH/CB-like chondrite formed before less refractory inclusions on the basis of their Al-Mg isotopic system and oxygen isotopic compositions. Recently, Krot and Nagashima (2009) (Krot et al 2006a).…”
Section: Pristine Nature Of Refractory Inclusions In Sau 290 and Compmentioning
confidence: 99%
“…The latter two characteristics suggest that CAIs in CH chondrites are more refractory and primitive than those in other chondrites (e.g., CV3 and CO3). However, some investigators (MacPherson et al 1989;Kimura et al 1993;Weber et al 1995;Krot et al 2008) found that most grossiteand hibonite-bearing CAIs lack excess of 26 Mg, the decay product of short-lived radionuclide 26 Al. Furthermore, CH CAIs have a bimodal distribution of oxygen isotopic compositions (Sahijpal et al 1999;Krot et al 2008) whereas oxygen isotopic compositions are homogeneous within individual CAI (Kimura et al 1993;Sahijpal et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation